Evaluation of a metagenomic detection technique for human enteric bacteria in retail chicken - Alexander, Faby R.; MK, Femina; Joseph, Sunu; Babu, Subramanian (Research in Biotechnology, 2012)
enteric bacteria in artificially contaminated chicken sample. Tests were performed in inoculated chicken samples using Salmonella enterica and Aeromonas hydrophila, with dilutions of 106,105,104 CFU/ml. We have developed a direct metagenomic (chicken DNA, inoculated bacterial DNA and endogenous microbial DNA if any) PCR technique for detection of bacteria from this food metagenome. Amplification of respective bacterial 16S rRNA region was performed. PCR conditions were optimized and amplification of Salmonella enterica specific DNA was achieved in all samples inoculated with different concentration of bacterial suspension. Aeromonas hydrophila infected tissues failed to reveal a specific amplification even after several modifications in gradient PCR.Ã‚Â  Interestingly, the control (uninoculated) chicken tissues also exhibited a less intense amplification of similar size DNA to target, indicating the possible endogenous contamination of the chicken meat obtained from the retail shop for our analysis.